2015
DOI: 10.1111/jsr.12301
|View full text |Cite
|
Sign up to set email alerts
|

Slow oscillating transcranial direct current stimulation during sleep has a sleep‐stabilizing effect in chronic insomnia: a pilot study

Abstract: SUMMARYRecent evidence suggests that lack of slow-wave activity may play a fundamental role in the pathogenesis of insomnia. Pharmacological approaches and brain stimulation techniques have recently offered solutions for increasing slow-wave activity during sleep. We used slow (0.75 Hz) oscillatory transcranial direct current stimulation during stage 2 of non-rapid eye movement sleeping insomnia patients for resonating their brain waves to the frequency of sleep slow-wave. Six patients diagnosed with either sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 39 publications
0
35
0
2
Order By: Relevance
“…Lastly, SWS is characterized by slow-wave oscillations (SWO), which decrease during the course of the night ( 67 ). tDCS applied during SWS reduces the decay of SWO ( 65 , 67 , 104 ), while anodal tDCS over frontocortical areas is beneficial to declarative memory when applied during SWS, an effect mediated by decreasing the rate of decrease of SWO ( 65 , 105 108 ). Taken together, these studies identify tDCS as a stand-alone intervention to enhance SWS and boost declarative cognitive and motor memory acquired during the day over subsequent sleep.…”
Section: Sleep As a Potential Modulator Of Tdcs-based Stroke Rehabilimentioning
confidence: 99%
“…Lastly, SWS is characterized by slow-wave oscillations (SWO), which decrease during the course of the night ( 67 ). tDCS applied during SWS reduces the decay of SWO ( 65 , 67 , 104 ), while anodal tDCS over frontocortical areas is beneficial to declarative memory when applied during SWS, an effect mediated by decreasing the rate of decrease of SWO ( 65 , 105 108 ). Taken together, these studies identify tDCS as a stand-alone intervention to enhance SWS and boost declarative cognitive and motor memory acquired during the day over subsequent sleep.…”
Section: Sleep As a Potential Modulator Of Tdcs-based Stroke Rehabilimentioning
confidence: 99%
“…While also confirming the increased frontal power of faster EEG frequencies, we argued in a recent paper that findings of decreased slow oscillation (0.3-0.79 Hz) power proportions during SWS in insomnia patients-while SWS duration was preserved in comparison to healthy controls-could indeed also come as a support to the former evidence of homeostatic dysfunction in insomnia (Neu et al, 2015). Following these findings of lowered slow oscillation power in insomnia, a small pilot study has even reported an increase in slow oscillation power during SWS after external stimulation with slow oscillations (<0.75 Hz) by means of transcranial direct current (Saebipour et al, 2015). Conversely, these effects were related to enhanced sleep stabilization and also seemed to be associated with improvements of subjective sleep quality (Saebipour et al, 2015).…”
mentioning
confidence: 62%
“…Following these findings of lowered slow oscillation power in insomnia, a small pilot study has even reported an increase in slow oscillation power during SWS after external stimulation with slow oscillations (<0.75 Hz) by means of transcranial direct current (Saebipour et al, 2015). Conversely, these effects were related to enhanced sleep stabilization and also seemed to be associated with improvements of subjective sleep quality (Saebipour et al, 2015). However, whether this increase of slow oscillations during SWS can remain stable over time, or whether daytime fatigue could improve concomitantly, remains unknown at present.…”
mentioning
confidence: 90%
“…These results suggest that tDCS may modulate sleepiness in idiopathic patients [55][56][57]. Emerging research has demonstrated that application of slow oscillatory tDCS compared to sham-slow oscillatory tDCS decreased waking time [58][59][60]. These findings suggest a putative sleep-stabilizing role for slow oscillatory after tDCS in insomniacs [61,62].…”
Section: Transcranial Direct Current Stimulation For Insomniamentioning
confidence: 73%